2013
DOI: 10.2478/afe-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

Mould Components Impact on Structure and Quality of Elektron 21 Alloy

Abstract: Magnesium alloys due to their low density and high strength-to-weight ratio are promising material for the automotive and aerospace industries. Many elements made from magnesium alloys are produced by means of sand casting. It is essential to investigate impact of the applied mould components on the microstructure and the quality of the castings. For the research, six identical, 100x50x20mm plates has been sand cast from the Elektron 21 magnesium casting alloy. Each casting was fed and cooled in a different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, the additions of Y to the Mg-Zn-Zr alloy result an increase in the volume fraction of the interdendritic compounds [3].SEM observations showed that the microstructure of base alloy consists of solid solution structure α-Mg grains, surrounded by intermetallic phase on grain boundaries. The EDS results for base alloy showed that the matrix consists of magnesium and a small amount of zirconium and binary phase Mg 3 (Nd, Gd) [18].SEM observation and EDS results of EV31A +1 Y alloy are shown in Fig ( 2). It showed that the EV31A +1 Y alloy consisted of two phases, the α-Mg matrix and intermetallic compound contain Mg,Gd,Nd,Zn,Zr,Y which means that Y combined with the intermetallic phase, thus continuously distributed along the grain boundaries.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the additions of Y to the Mg-Zn-Zr alloy result an increase in the volume fraction of the interdendritic compounds [3].SEM observations showed that the microstructure of base alloy consists of solid solution structure α-Mg grains, surrounded by intermetallic phase on grain boundaries. The EDS results for base alloy showed that the matrix consists of magnesium and a small amount of zirconium and binary phase Mg 3 (Nd, Gd) [18].SEM observation and EDS results of EV31A +1 Y alloy are shown in Fig ( 2). It showed that the EV31A +1 Y alloy consisted of two phases, the α-Mg matrix and intermetallic compound contain Mg,Gd,Nd,Zn,Zr,Y which means that Y combined with the intermetallic phase, thus continuously distributed along the grain boundaries.…”
Section: Resultsmentioning
confidence: 95%